Illocutionary Acts Used by Main Character of Zootopia - Sarair, Sarair; Farsia, Lina; Jannah, Lena Miftahul (ACCENTIA: Journal of English Language and Education, 2021)
The way people connect with one another is referred to as communication. People interact to communicate things like asking, asserting, promising, thanking, apologizing, and complaining. Thus, utterances have a purpose in communication. The goal of this study was to identify the sorts of illocutionary acts used in Zootopia. Specifically, the study examined any illocutionary acts found in the main characters utterances. This qualitative study used descriptive methods as a technique analysis. The study also used documentary techniques and classification methods to analyze the data obtained. The data were the utterances of the main character, Judy Hopps. The results of this study revealed that the speeches of the main character contained five categories of illocutionary acts: representative acts, directive acts, commissive acts, expressive acts, and declarative acts. In addition, the most illocutionary acts used were the expressive acts. Thus, it can be concluded that the type of illocutionary acts that appears the most in the speeches of the main character is the expressive acts.